Critical terrorism studies since 11 September 2001 : what has been learned? - Blackbourn, Jessie; Dexter, Helen; Dhanda, Rani; Miller, David (Abingdon, Oxon Routledge, 2014)
Academic studies of terrorism grew exponentially in number after the September 11 attacks. More than a decade since the founding of the critical project, this asks what has been learned. Showcases leading examples of critical terrorism studies & presents an agenda for an evidence-based approach to political violence & terrorism.
Academic studies of terrorism grew exponentially in number after the September 11 attacks. More than a decade since the founding of the critical project, this asks what has been learned. Showcases leading examples of critical terrorism studies & presents an agenda for an evidence-based approach to political violence & terrorism. Miller at UNSW.
1.Introduction: Editor's Introduction: A decade on from 11 September 2001: what has critical terrorism studies learned? / David Miller -- 2.Unknown knowns: the subjugated knowledge of terrorism studies / Richard Jackson -- 3.Don't confuse me with the facts: knowledge claims and terrorism / Michael Stohl -- 4.Drones, witches and other flying objects: the force of fantasy in US counterterrorism / Joseba Zulaika -- 5.Reinventing prevention or exposing the gap? False positives in UK terrorism governance and the quest for pre-emption / Charlotte Heath-Kelly -- 6.Social cohesion and the notion of{u1833}uspect communities': a study of the experiences and impacts of being{u1833}uspect' for Irish communities and Muslim communities in Britain / Sara Silvestri -- 7{u1B85}vents dear boy, events': terrorism and security from the perspective of politics / Andrew W. Neal -- 8.Terrorism and violence: another violence is possible? / Helen Dexter.
Includes bibliographical references and index.
Keywords: International relations; Security, International; Terrorism -- Prevention -- Evaluation; War on Terrorism, 2001-2009 -- Influence